PROPOSED MARKETING STRATEGY FOR HOTEL BUSINESS AT INTEGRATED BUILDING SOEKARNO HATTA AIRPORT (The Indonesian Journal of Business Administration, 2019)
PT Angkasa Pura II (Persero) through PT Angkasa Pura Propertindo as a subsidiary is currently in the construction phase of a hotel located in the Integrated Building area of Soekarno Hatta Airport. This activity as one of the company’s efforts in business development an to increase non-aero revenue to achieve the 11.4T revenue target by developing support from subsidiaries.This study analyses the marketing strategy of the Integrated Building Hotel in the midst of hotel competition around the existing Soekarno Hatta Airport area and how PT APP’s strategy as a hotel business manager can seize the hotel business market and compete in the hotel business to increase PT AP2’s non-aero revenue as a result of developing support for a subsidiary of PT APP.The theoretical approach used are external analysis consisting of the general environment, industrial environment, competitor analysis, customer analysis, and internal analysis. Then the result of the analysis are categorized using a SWOT analysis. The process starts with finding a TOWS analysis solution. The marketing strategy is obtained by considering and using the results of the analysis of various previous factors by designing proposal for the development of Segmentation, Targeting, and Positioning (STP), and Integrated Building Hotel Marketing Mix.Keyword: Integrated Building Hotel, Marketing Strategy, TOWS, STP, Marketing Mix.